Determining programmed cell death ligand 1 expression in circulating tumor cells of patients with clear cell renal cell carcinoma and its correlation with response to programmed cell death protein 1 inhibitors. (7th February 2022) - Chen, Bo‐Han; Kao, Chien‐Chang; Xu, Ting; Yang, Yung‐Ning; Cha, Tai‐Lung; Tsai, Yi‐Ta; Liu, Shu‐Yu; Wu, Sheng‐Tang; Meng, En; Tsao, Chih‐Wei; Chen, Chin‐Li; Sun, Guang‐Huan; et al.
Abstract : Objective: There is a great interest in determining whether the expression of the programmed cell death ligand 1 is correlated with the efficacy of immune checkpoint inhibitors in patients with clear cell renal cell carcinoma; however, primary tumor biopsies can only provide limited information. Therefore, we explored the expression of programmed cell death ligand 1 on circulating tumor cells, which is a potential predictor of therapeutic response. Methods: Circulating tumor cells were isolated from 20 clear cell renal cell carcinoma patients based on cell surface markers targeting clear cell renal cell carcinoma using IsoFlux device, followed by identification according to cell morphology and immunofluorescence studies. Programmed cell death ligand 1 expression status and clinical correlations were also analyzed. Results: Before treatment with programmed cell death protein 1 inhibitors, circulating tumor cells were detected in all patients, ranging from 1 to 22 (median 7), with 75% (15/20) of the patients having programmed cell death ligand 1 + circulating tumor cells. Circulating tumor cell programmed cell death ligand 1 expression did not correlate with the immunohistochemical staining of programmed cell death ligand 1 in primary tumors. During treatment with programmed cell death protein 1 inhibitors, the disease control rate was much higher in the patients harboring programmed cell death ligand 1 + circulating tumor cells (73%, 11/15) than others (20%, 1/5). We also found that changes in total circulating tumor cell numbers and programmed cell death ligand 1 + circulating tumor cell counts correlated well with the disease outcome. Conclusion: We showed that the presence of programmed cell death ligand 1 + circulating tumor cells before programmed cell death protein 1 inhibition treatment could be a prognosis predictive factor and that the dynamic changes in circulating tumor cell numbers may be used to monitor the therapeutic response. Our study confirms the possibility of programmed cell death ligand 1 + circulating tumor cell detection in clear cell renal cell carcinoma patients' blood samples, which can potentially be used as an individualized immunotherapy molecular biomarker for real‐time exploration.